Persistence of High Percentage of Peripheral Activated CD8+ T Cells Predict Cytologic HPV-Related Dysplasia in cART-Treated, HIV-Positive Subjects. (30th January 2022) - Mondatore, Debora; Bai, Francesca; Augello, Matteo; Giovenzana, Marco; Pisani Ceretti, Andrea; Bono, Valeria; Opocher, Enrico; d'Arminio Monforte, Antonella; Marchetti, Giulia Carla; Tincati, Camilla
Abstract: Background: People with HIV are at increased risk of human papillomavirus (HPV) disease progression, given the persistence of immune activation and residual inflammation despite effective combination antiretroviral therapy (cART). Whether a low CD4:CD8 T-cell ratio, known to mirror peripheral immune dysfunction, is associated with squamous intraepithelial lesions (SILs) is unknown. Methods: This was a retrospective cohort study on cART-treated HIV-positive subjects undergoing screening for HPV-related dysplasia (anal/cervical cytology and HPV genotyping). SIL was defined as the presence of either atypical squamous cells of undetermined significance (ASCUS), low-grade SILs, or high-grade SILs. Demographic and viro-immunological parameters (T-cell count, CD4:CD8 T-cell ratio, CD8+ CD38+ T-cell percentage) at the time of screening were analyzed by the chi-square test, Mann-Whitney test, and multivariate logistic regression analysis. Results: A total of 419 cART-treated subjects were included. Half of the patients had cervical/anal SIL. Individuals with SIL were more commonly males, were men who have sex with men, were coinfected with Treponema pallidum, had been treated with integrase inhibitor (INSTI)–based cART regimens, and had a shorter time since HIV diagnosis and cART initiation than subjects with normal cytology. CD38+ CD8+ T-cell percentage, but not the CD4:CD8 T-cell ratio, correlated with SILs. HPV infection, especially with multiple and high-risk genotypes, was confirmed to be associated with SIL. In multivariate analysis, the only factors independently associated with cervical/anal dysplasia were HPV infection and harboring higher percentages of peripheral activated CD38+ CD8+ T cells. Conclusions: HPV infection is the major driver of dysplasia in the setting of HIV infection. In this study, CD8+ CD38+ T cells were an independent predictor of dysplasia in cART-treated subjects, while CD4:CD8 T-cell ratio was not. In the setting of HIV–HPV coinfection, CD4:CD8 T-cell ratio may not fully capture the alterations of HPV-specific immunity.